2016
DOI: 10.1111/ajt.13525
|View full text |Cite
|
Sign up to set email alerts
|

Protein Quantitative Trait Loci Analysis Identifies Genetic Variation in the Innate Immune Regulator TOLLIP

Abstract: Summary We previously identified plasma plasminogen activator inhibitor-1 (PAI-1) level as a quantitative lung injury biomarker in PGD. We hypothesized plasma levels of PAI-1 used as a quantitative trait could facilitate discovery of genetic loci important in PGD pathogenesis. A 2-stage cohort study was performed. In stage 1, we tested associations of loci with PAI-1 plasma level using linear modeling. Genotyping was performed using the Illumina CVD Bead Chip v2. Loci meeting a p<5×10−4 cutoff were carried for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Likewise, mirroring our blood findings, Nod-like receptor (NLR), toll-like receptor (TLR), and myeloid differentiation primary response gene 88 (MyD88) pathways were among the most highly ranked gene sets in patients with PGD in an analysis of BAL fluid gene expression in a nested population from this CTOT 03 study 7 . Recipient genetic variation in toll-interacting protein ( TOLLIP ), a regulator of innate inflammatory TLR signaling cascades, is also significantly associated with risk for PGD after lung transplantation 21 . Taken together, the pathways identified in our current and previous studies indicate that inflammasome and innate immune activity are upregulated both locally in the allograft and systemically in the recipient in patients with PGD, thus providing further evidence that innate immune and inflammasome signaling pathways are novel targets for future PGD preventative and therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, mirroring our blood findings, Nod-like receptor (NLR), toll-like receptor (TLR), and myeloid differentiation primary response gene 88 (MyD88) pathways were among the most highly ranked gene sets in patients with PGD in an analysis of BAL fluid gene expression in a nested population from this CTOT 03 study 7 . Recipient genetic variation in toll-interacting protein ( TOLLIP ), a regulator of innate inflammatory TLR signaling cascades, is also significantly associated with risk for PGD after lung transplantation 21 . Taken together, the pathways identified in our current and previous studies indicate that inflammasome and innate immune activity are upregulated both locally in the allograft and systemically in the recipient in patients with PGD, thus providing further evidence that innate immune and inflammasome signaling pathways are novel targets for future PGD preventative and therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…32 Notably, those findings from experimental models of lung IRI are consistent with recent human genomic studies of PGD. 11,23 …”
Section: Alveolar Macrophagesmentioning
confidence: 99%
“…8 Janeway and Medzhitov showed that DAMPs, along with pathogen-associated molecule patterns (PAMPs), are recognized by pattern recognition receptors (PRRs) that, when engaged, stimulate inflammatory gene expression. 9 Later reports showed DAMP accumulation and the involvement of PRR signaling pathways in PGD patients, but precisely how they contribute to this type of acute lung injury remains an active area of investigation, 3,10,11 as lung IRI also may be influenced by PAMPs derived from the gut microbiota. 12 In addition, the recent availability of multicenter-derived lung transplant recipient outcome data in conjunction with transcriptome and genomic analysis and new experimental approaches has identified additional mechanisms that could promote PGD.…”
mentioning
confidence: 99%
“…A variety of clinical risk factors for PGD have been identified with contributions from the donor (3)(4)(5)(6)(7), the recipient (3)(4)(5)(7)(8)(9)(10), and operative variables (4,5,8,11). In addition, a number of biomarkers have been associated with increased risk of PGD, including markers of innate and adaptive immune activation, epithelial and endothelial injury, coagulation, vascular permeability, and lipid peroxidation (2,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Despite identification of these clinical and biomarker predictors of PGD, the mechanisms leading to PGD are not well understood, and there are no specific therapeutic interventions for PGD.…”
Section: Introductionmentioning
confidence: 99%